2022
DOI: 10.1002/jnr.25021
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids improve the stability and function of P23H rhodopsin slowing down the progression of retinitis pigmentosa in mice

Abstract: The balanced homeostasis of the G protein–coupled receptor (GPCR), rhodopsin (Rho), is required for vision. Misfolding mutations in Rho cause photoreceptor death, leading to retinitis pigmentosa (RP) and consequently blindness. With no cure currently available, the development of efficient therapy for RP is an urgent need. Pharmacological supplementation with molecular chaperones, including flavonoids, improves stability, folding, and membrane targeting of the RP Rho mutants in vitro. Thus, we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Moreover, CR5 prolonged the survival of photoreceptors in RP-related knock-in P23H mice, likely due to its ability to increase the conformational stability of mutated rod opsin, which assisted the correct folding and transport of the mutant receptor. As we recently demonstrated, quercetin provided similar advantageous effects slowing the progression of RP in these mice (19).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Moreover, CR5 prolonged the survival of photoreceptors in RP-related knock-in P23H mice, likely due to its ability to increase the conformational stability of mutated rod opsin, which assisted the correct folding and transport of the mutant receptor. As we recently demonstrated, quercetin provided similar advantageous effects slowing the progression of RP in these mice (19).…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, we recently found that polyphenolic compounds such as flavonoids bind to rod opsin and enhance its stability (18). For instance, quercetin restores multiple native interactions within the chromophore-binding site of the P23H rod opsin and improves the function of this mutant in vitro (19). Moreover, treatment with quercetin prevents retinal degeneration caused by excessive accumulation of unliganded opsin upon exposure to bright light and importantly slows the progression of photoreceptor cell death in the P23H Rho knock-in mouse model of RP (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations